The impact of food for education programs in Bangladesh - Ahmed, Akhter; Babu, Suresh Chandra (Cornell University, 2007)
Educating children can help them and their families to move out of poverty. Yet even with free tuition, the cost of attaining education remains high for poor families in developing countries owing to competing demands on children’s time and other associated costs. One way to attract children from poor households to school, and keep them in school, is to provide food as an incentive for attendance. Food for education (FFE) programs provide immediate sustenance for the hungry, but perhaps more important, they empower future generations by educating today’s children. This case study from Bangladesh provides evidence of the impact of FFE interventions in enhancing educational attainment and improving nutrition and describes the movement forward and the challenges ahead. The study also reviews the impact of FFE programs in other countries. FFE programs include interventions that feed children in school and those that give food to poor families if they send their children to school. The design, implementation, and impacts of FFE programs vary depending on many factors and from country to country. A review of international experience with the impacts of FFE programs shows that they have been successful in improving educational attainment, dietary intake, nutritional status, and academic performance of participating children. FFE programs are increasingly attractive to policy makers because they address the two major human development goals: education and nutrition. Yet several operational, budgetary, and political economy considerations need to be addressed to improve the efficacy of these programs. The government of Bangladesh has tried two types of food-based interventions to increase primary education and food security of poor households. Your assignment is to recommend changes in the FFE program in Bangladesh, including possibly the scaling up of the programs, taking into account expected benefits and leakages. Discuss the policy options that the government of Bangladesh can consider in implementing a new FFE program, but which some stakeholders might resist. Justify your recommendations in light of the consequences for the various stakeholders.